PENGEMBANGAN MEDIA INTERAKTIF BERBASIS SMART APPS CREATOR (SAC) PADA MATA PELAJARAN IPAS KELAS IV SD - Tri Yowanda Sari; Ida Suryani; Jayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Based on the problem at SD Negeri 23 Palembang, there has been no use of interactive media based on Smart Apps Creator (SAC) and learning is still monotonous because it still uses media that is only pasted which results in less interesting learning so that students feel bored. This research aims to produce interactive media products based on Smart Apps Creator (SAC) in science subjects in grade IV elementary school that are valid and practical. The type of research used is Research and Development (R&D) using the ADDIE model. This development resulted in a product in the form of an application that can be installed through android. The results of the interactive media research based on Smart Apps Creator (SAC) there are 3 validation experts, a) media experts obtained a score of 94.6% with the description